Honorary Teacher Well-Being: An Analysis of the Relationship with Transformational Leadership and Work Stress - Wakhid, Ali Abdul; Suhandi, Suhandi; Erwanto, Erwanto; Shumaila, Shumaila (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Teacher well-being is often discussed in Indonesia in terms of the salaries and incentives they receive. However, there is another aspect of well-being that is rarely discussed, especially in the context of teachers in Indonesia, known as teacher well-being. The purpose of this study was to investigate the relationship between transformational leadership and job stress on teacher well-being in honorary teachers. The subjects in this study consisted of 32 honorary teachers. The data analysis method in this study applied multiple regression analysis with the support of JASP 0.19.1.0 software for Windows. The findings of this study indicate that principals' transformational leadership and job stress jointly influence teachers' welfare in honorary teaching staff with a value of r=0.787 and p<0.001, where the effective contribution reaches 78.8%, while the other 21.3% is influenced by other variables not analyzed in this study. The impact of this study can be a guideline for schools in formulating leadership strategies and building a more supportive work atmosphere for teacher welfare to improve the quality of education and reduce the stress experienced by honorary teachers.Kesejahteraan guru yang sering dibahas di Indonesia adalah dari segi gaji serta insentif yang mereka terima. Namun, ada aspek kesejahteraan lain yang masih jarang dibahas, terutama dalam konteks guru di Indonesia, yang dikenal dengan istilah teacher well-being. Tujuan dari penelitian ini adalah untuk menginvestigasi hubungan antara kepemimpinan transformasional dan stres kerja terhadap kesejahteraan guru pada pengajar honorer. Subjek dalam penelitian ini terdiri dari 32 guru honorer. Metode analisis data dalam penelitian ini menerapkan analisis regresi berganda dengan dukungan perangkat lunak JASP 0.19.1.0 untuk Windows. Temuan dari penelitian ini menunjukkan bahwa kepemimpinan transformasional kepala sekolah serta stres kerja berpengaruh secara bersama-sama terhadap kesejahteraan guru pada tenaga pengajar honorer dengan nilai r=0.787 dan p<0.001, di mana kontribusi efektifnya mencapai 78.8%, sedangkan 21.3% lainnya dipengaruhi oleh variabel lain yang tidak dianalisis dalam studi ini. Dampak dari penelitian ini bisa menjadi pedoman bagi sekolah dalam merumuskan strategi kepemimpinan dan membangun suasana kerja yang lebih mendukung kesejahteraan guru untuk meningkatkan mutu pendidikan dan mengurangi stres yang dialami oleh guru honorer.